Numerical study of natural convection in nanofluids using a novel approach to thermophysical properties: Application to Cu-based core-shell nanoparticles with single and double shell structures - Kabache, Malika; Iachachene, Farida; Mougari, Nour Elislam; Cheradi, Hanane; Dalkilic, Ahmet Selim (SAGE PUBLICATIONS LTD, 2025)
Natural convection is a crucial heat transfer mechanism in electronics cooling and energy systems. Nanofluids, utilizing various types of nanoparticles, have been found to significantly improve thermal performance, making them promising candidates for enhancing this process. In this study, a novel type of hybrid core-shell nanoparticle and a new approach to define the thermophysical properties of these nanofluids for enhancing heat transfer in a differentially heated square cavity, were introduced. The novelty of this work lies in the adoption of new correlations to simulate the thermophysical properties of core-shell nanoparticles, tailored for both single and double shell structures. Copper-based nanoparticles with single or double shells (Cu@Ag, Cu@Au, and Cu@Ag-Au) suspended in water were used to examine the influence of Rayleigh numbers (Ra) and nanoparticle concentrations (phi) on heat transfer. A correlation for the thermal conductivity of the nanofluid ( k nf ) has been developed based on existing data, taking into account the thermal conductivities ( k p ) of both the core and shell of the nanoparticles. The numerical simulations employ the finite volume method to discretize the continuity, momentum, and energy equations, using the Boussinesq approximation to model buoyancy effects. To confirm the accuracy of the numerical approach and the mathematical model, a thorough series of comparisons was carried out for free convection in a square cavity under differential heating circumstances. Several researchers' experimental data from the literature were used to comprehensively assess the correctness of the numerical solutions and simulations. The results show that Cu@Au-water nanofluids can achieve up to a 74.83% increase in Nusselt number over pure water at Ra = 106 and phi = 0.03, followed closely by Cu@Ag-Au, which exhibits a 54.32% improvement. The study highlights the potential of core-shell nanofluids, specifically Cu@Au, in improving thermal performance in advanced thermal management applications, paving the way for future optimization of multi-layered nanoparticles.
Keywords: Core-shell nanoparticles; hybrid nanoparticles; thermal conductivity; natural convection; heat transfer enhancement; THERMAL-CONDUCTIVITY; HEAT-TRANSFER; FLOW; SUSPENSIONS; VISCOSITY; CAVITY; Engineering